The Future of Citizenship: Global and Digital – A Rejoinder - Liav Orgad (Debating transformations of national citizenship, 2018)
We can construct theoretical models of digital citizenship but, as this debate has shown, there are plenty of uncertainties – political, technological, and psychological ones – before it can become actually operative. I agree with Milan that `much work is needed … before we can proclaim the blockchain revolution.' In particular, I share the concern about global inequality generated by ideas of cloud communities due to lack of internet access (Dzankic, Ypi, Kochenov) – this gap, however, has tremendously (and rapidly) narrowed and in 104 states more than 80 per cent of the youth population (aged 15–24) are now online. The situation will further improve if a right to internet access is universally recognised. And I cannot but share Bauböck's worries about the tyranny of the majority in the cloud – addressing it is a matter of constitutional design of voting mechanisms (note, however, that there will be judicial review, decisions that require supermajority, and perhaps even veto rights in the digital world as well). Discussing these (and others) concerns will keep theorists and policy makers busy in the years to come. While the focus of this debate is on global citizenship and virtual communities, I see it as a broader invitation to reflect on the nexus between new technologies and the future of citizenship.
Keywords: 330